Implementation and evaluation of workflow based on hospital information system/radiology information system/picture archiving and communications system...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Osada M; Nishihara E (Journal of Digital Imaging)
The purpose of this presentation is to review and evaluate computerized workflow of selected sites that have integrated systems of the hospital information system (HIS), radiology information system (RIS), and picture archiving and communications system (PACS). We then focus on some essential points of integration of those systems, such as avoiding multiple entries of patients demographic data, prefetching current and previous images to the correspondent workstations, and workflow management. To realize them by integrating multiple subsystems such as HIS/RIS/PACS integration, there must be exchange of the workflow control information, and consistency of the information between subsystems. Copyright (c) 1999 by W.B. Saunders Company